Gölcük (Kocaeli/Türkiye) Bitki örtüsünün fitoekolojik ve fitososyolojik yönden araştırılması - (:unkn) unknown (My University, 2012)
Bu çalışma, Gölcük (Kocaeli/Türkiye) bitki örtüsünün fitoekolojik ve fitososyolojik özelliklerini tespit etmek ve sintaksonomisini yapmak amacıyla gerçekleştirilmiştir. Alan çalışmaları, 2005-2007 yılları arasında klasik Braun-Blanquet metodu uygulanarak yapılmıştır. Araştırma bölgesinde maki vejetasyonuna ait 2 ve orman vejetasyonuna ait 3 birlik, tespit edilmiştir. Dördü yeni olan bu birliklerin betimlemesi, tipifikasyonu ve sintaksonomisi yapılmıştır. Birlikler, benzer birlikler ile fitososyolojik ve fitoekolojik bakımından kıyaslanarak tartışılmıştır. Tanımlanan birlikler aşağıdaki gibidir: Maki Vejetasyonu, 1. Birlik: Ferulago confusae-Quercetum cocciferae ass. nova 2. Birlik: Erico arborae-Phillyretum latifoliae ass. nova Orman Vejetasyonu, 3. Birlik: Carici serratulae-Quercetum ibericae ass. nova 4. Birlik: Smilaco-Castanetum sativae Ketenoğlu, Tuğ ve Kurt 2010 5. Birlik: Cardamino tenerae-Fagetum orientalis ass. nova

This study was conducted to determine the phytoecological and phytosociological characteristics of the vegetation which is distributed in Golcuk District (Kocaeli/Turkey) and put forward its syntaxonomy. Field studies has been carried out by using the classic Braun-Blanquet method in the years of 2005-2007. Two associations belonging to macchia vegetation and three associations belonging to forest vegetation were determined from the investigation area. Four of these associations are new and their description, typification and syntaxonomy has been done. Phytosociological and phytoecological features of these associations were discussed and compared to their relatives. The associations described are as follows: Maquis vegetation, 1. Associations: Ferulago confusae-Quercetum cocciferae ass. nova 2. Associations: Erico arborae-Phillyretum latifoliae ass. nova Forest vegetation, 3. Associations: Carici serratulae-Quercetum ibericae ass. nova 4. Associations: Smilaco-Castanetum sativae Ketenoglu, Tug and Kurt 2010 5. Associations: Cardamino tenerae-Fagetum orientalis ass. nova
Phytoecological and phytosociological ınvestigations of the vegetation of Golcuk (Kocaeli/Turkey)
Keywords: Biyoloji